Effect of Mn and Cr on structure and mechanical properties of Al-10%Mg-0.1%Ti alloy. (September 2018) - Alizadeh Razazi, Hossein; Paidar, Moslem; Ojo, Olatunji Oladimeji
Abstract: This study examines the effect of different concentrations of Cr and Mn on the microstructure and mechanical properties of Al-10%Mg-0.1%Ti Alloy by using Al-10Cr and Al-10Mn master alloys. The microstructures were studied via the aid of an optical microscope (OM), X-ray diffraction (XRD) and energy dispersive X-ray (EDS) integrated with scanning electron microscopy (SEM). Cr and Mn contents promote the formation of Al7 Cr and Al11 Cr2, and Al6 Mn phases in the structures of the alloy. The mechanical properties of the alloy increase with Mn content (0.5–3 wt%) due to grain refining and dispersion hardening effect of Al6 Mn while higher Cr content precipitates deleterious secondary brittle phase of Al11 Cr2 . Cr and Mn contents beyond 1 and 3 wt% deteriorate the ultimate tensile strength (UTS) and percentage elongation of the as-cast alloy due to the presence of higher area fraction of brittle intermetallic phases. A direct relationship exists between hardness values and the addition of Cr and Mn contents. Low and high Cr and Mn contents show ductile and brittle fracture modes. Highlights: A direct relationship exists between hardness values and the addition of Cr and Mn contents. The formation of needle-shape precipitate begins in the alloy from the addition of 2 wt% Mn and beyond. The addition of Mn (up to 3 wt%) refines the average grain size of the Al-10%Mg-0.1%Ti alloy. Increase in Mn content has a positive effect on both the UTS and percentage elongation of the alloy. Grain refining effect of Mn and dispersion hardening effect of Al6 Mn dispersoids are responsible for the improved properties. Optimum values of mechanical properties of 228 MPa and 4.1 % were obtained at Mn content of 3% while the addition of 1 wt% Cr produced optimum values of 250 MPa and 8.8 %.